2022
DOI: 10.1108/jcm-07-2020-3981
|View full text |Cite
|
Sign up to set email alerts
|

Dark triad-consumer behavior relationship: the mediating role of consumer self-confidence and aggressive interpersonal orientation

Abstract: Purpose This study aims to investigate the consumer behavior of the Dark Triad (DT) personality traits. It investigates the sequential mediating role of consumer self-confidence and aggressive interpersonal orientation in the relationship between the DT personality traits (i.e., narcissism, psychopathy and Machiavellianism) and consumer behavior. Design/methodology/approach Using identity theory as a theoretical framework, the authors develop and assess a model linking the DT personality traits to consumer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…However, some negative reports or news reports with exaggerated elements will affect managers’ emotions, shake managers’ confidence, and reduce investment efficiency. Blair et al (2022) verified the market pressure hypothesis of the media from an audit perspective. The media can enhance the power of external audit, reduce the motivation of enterprise profit management, and effectively realize the role of enterprise governance.…”
Section: Literature Reviewsupporting
confidence: 54%
See 1 more Smart Citation
“…However, some negative reports or news reports with exaggerated elements will affect managers’ emotions, shake managers’ confidence, and reduce investment efficiency. Blair et al (2022) verified the market pressure hypothesis of the media from an audit perspective. The media can enhance the power of external audit, reduce the motivation of enterprise profit management, and effectively realize the role of enterprise governance.…”
Section: Literature Reviewsupporting
confidence: 54%
“… Greo (2021) and Mundi and Kaur (2022) pointed out that managers with overconfidence will be keen on enterprise expansion strategies and realize enterprise expansion by increasing investment in mergers and acquisitions, but the result will increase the possibility of companies falling into financial crisis. Blair et al (2022) refined the scope of investment and defined it as the investment in fixed assets by enterprises. The results found that the higher the level of managers’ overconfidence, the more investment in fixed assets by enterprises.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Narcissism and Machiavellianism act differently. Past research purported a wide overlap between the personalities of narcissism and Machiavellianism and in certain scenarios, but past researchers have not been distinct in analyzing their impact on their considered outcomes (Gala et al , 2020; Blair et al , 2022). Our research finds an exclusive behavior of these two personalities wherein they are not similar to each other.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Similarly, narcissists have also been known to demonstrate a negative relationship with ethical decision-making (Antes et al , 2007). However, the reasoning behind the unethical behavior differs between these two personality styles, with narcissists being primarily motivated by opportunities to self-promote and Machiavellians motivated by potential benefits to their own agendas (Gnambs and Appel, 2018; Jones and Paulhus, 2009; Lee and Ashton, 2017; Blair et al , 2022). Thus, understanding their interaction with relativism/idealism would bring a unique contribution to the literature, proving how they work in tandem to influence CEB.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Akintimehin et al (2022) investigated CA towards ethical consumption to engage in ethical consumption behaviour by consumers. Blair et al (2022) investigated the relationship between consumers' personality traits and CB and found positive significance. So, consumers may base their purchase decisions on their attitudes towards the environment and socially responsible retailers.…”
Section: Impact Of Consumer Attitude On Consumer Purchasing Behaviourmentioning
confidence: 99%